EFFECT OF PHOSPHORUS AND SULPHUR APPLICATIONS ON GROWTH, YIELD AND QUALITY OF TOMATO IN CALCAREOUS SOIL - KALPANA*, P. R.; KANTESH GANDOLKAR, R. SUMA,; KUMAR, S. KIRAN (The Bioscan, 2016)
The present study was conducted to examine the effect of phosphorus and sulphur applications on growth, yield and quality of tomato in medium black calcareous clay loam soil. Phosphorus (P) was tested at rates of 312.5, 250, 187.5, 125 and 0 kg ha-1 in combination with sulphur (S) applied at rates of 2.5, 1.5, 0.5 and 0 percent equivalent to calcium carbonate content in calcareous soil. Increased rate of P and S applications enhanced the tomato growth recording maximum height (86.53 cm), internode length (7.54 cm), branches per plant (9.75) and flowers per cluster (7.49) in treatment receiving P312.5+ S2.5. However, highest fruit setting rate (69.37%), number of fruits per cluster (4.94), fruits per plant (41.17), fruit weight (77.60 g) and fruit diameter (5.17cm) was obtained with application of P250+S2.5. Hence, application of 250 kg/ha Phosphorus along with 2.5 per cent S equivalent to CaCO3 content in calcareous soil was found ideal for tomato, that resulted in maximum fruit yield (3.19 kg plant-1) and better fruit quality viz., total soluble solids (4.71oBx), ascorbic acid (17.43 mg 100g-1) and â-carotene (3.61 mg 100 g-1) content.